The prolonged X-ray flaring activity of Mrk 501 in 2014. Issue 2 (17th April 2017) - Kapanadze, B.; Dorner, D.; Romano, P.; Vercellone, S.; Mannheim, K.; Lindfors, E.; Nilsson, K.; Reinthal, R.; Takalo, L.; Kapanadze, S.; Tabagari, L.
Abstract: The X-ray variability of the BL Lacertae source Mrk 501 was studied during 11.5 yr of monitoring with Swift . Here, we report the results of this study pertaining to the epoch of 2014 March–October, when our target showed the most powerful and long-lasting X-ray flaring activity. This epoch was characterized by X-ray flares varying in amplitude by factors of 2–5 on time-scales of a few weeks or shorter. We detected 35 instances of the intraday variability, sometimes occurring within the 1 ks observational runs. The X-ray flux was generally correlated with the TeV flux, while the 0.3–300 GeV and optical-UV fluxes did not show a significant correlation. Some notable incidences of more complicated variability patterns could also be recognized, indicating that the high-energy emission in Mrk 501 arose from an emission region more complex than a single zone. The best fits of the 0.3–10 keV spectra were mainly obtained using the logparabola model. Strong spectral variability was detected, affecting the slope but not the curvature of the spectrum. In strong flares, the spectral index became harder than 1.70. The spectral evolution was characterized by a harder-when-brighter behaviour, shifting the peak of the spectral energy distribution by about 20 keV that happens rarely in blazars.